Genetic study to bacteria Acinetobacter baumannii - Lactamase producer - Ali, Rasah Abid (Al-Nahrain Journal of Science, 2010)
Six isolates were collected from different clinical sources from laboratory in medicine century.These isolates were belonging to the genus Acinetobacter depending on morphological andbiochemical tests. The antibiotic susceptibility tests against 8 antibiotics were examined, and it wasfound that the all isolates have multiple resistant to antibiotic, all isolates were resistant toampicillin, ceftriaxone, cefotaxime, 50% were resistant to augmentin, 20% were resistant tociprofloxacin ,while 10% from isolates show resistant to amikacin and trimethprim. All isolateshave sensitivity to imipenem. The ability of Acinetobacter isolates to produce -lactamase enzymeswas, tested using iodometric method, and the results showed that all isolates produced this enzyme.The ability of these isolates to produce extended spectrum -lactamase (ESBLs) were alsodetermined by double disc synergy test, only one isolates produced these enzyme. Agarose gelelectrophoresis showed that Acinetobacter isolates -lactamase producer have two small plasmidbands. Transformation experiments revealed that these plasmids were capable to transform E. coliMM294, an observation which indicates the ability of these plasmids to show their expression inmore than one host.